El papel del obispo Donato de Cartago en la controversia arriana del siglo IV - Fernández, Gonzalo (Estudios humanísticos. Geografía, historia y arte, 1996)
This article deals with Bishop Donatus of Carthage's attitude in front of Arianism. The sources are an inscription published by J. Zeiller and literary. The literary sources belong to Hilary of Potiers, Jerome, Augustine of Hippo, Athanasius of Alexandria and the synodal epistle of a roman council in year 378 A. C. edited by J. D. Mansi.